2003
DOI: 10.1002/ajim.10304
|View full text |Cite
|
Sign up to set email alerts
|

Fatal injuries to teenage construction workers in the US

Abstract: Fatal injuries in teenage construction workers differed from those in adults in that they were more likely to be at small, non-union firms of which a substantial proportion were exempt from federal enforcement of child labor laws and from routine OSHA inspections. Safety programs for young construction workers should include small, non-union construction firms and those in special construction trades such as roofing. We did not identify specific areas for new regulation but the number of fatalities reviewed wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 2 publications
0
27
0
1
Order By: Relevance
“…Suruda et al observed in their findings that nearly 49% of fatal injuries occurred among 76 young construction workers. 9 Tiwary et al reported that 47% subjects of the construction workers in Kolkata were victims to injuries/accidents. 10 The injuries were due to cut by sharp objects (54.2%), falling of objects from height (22.5%) and fall from height (15.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Suruda et al observed in their findings that nearly 49% of fatal injuries occurred among 76 young construction workers. 9 Tiwary et al reported that 47% subjects of the construction workers in Kolkata were victims to injuries/accidents. 10 The injuries were due to cut by sharp objects (54.2%), falling of objects from height (22.5%) and fall from height (15.8%).…”
Section: Discussionmentioning
confidence: 99%
“…As an additional sub-group, young male workers may be especially vulnerable to workplace injuries and fatalities due to their limited work experience and their increased likelihood of being employed in smaller companies, which may not be subjected to the same OH&S standards (Breslin and Polzer, 2007;Breslin and Smith, 2005;Breslin and Mustard, 2003;Mitchell et al, 2002;Zakocs et al, 1998;Suruda et al, 2003). Young workers may also experience greater vulnerable to institutional pressures to accept and normalize occupational risks.…”
Section: Acceptance and Normalization Of Riskmentioning
confidence: 99%
“…These results indicate that young landscapers are at increased risk compared to young workers in other industries. Teen worker fatalities have been investigated in potentially dangerous industries such as construction, home building, farming, and agriculture [Schulman et al, 1997;Lipscomb and Li, 2001;Bonauto et al, 2003;Suruda et al, 2003;Runyan et al, 2006]. Although no prior studies have focused on fatalities among young landscapers, research has been conducted on non-fatal injuries.…”
Section: Agementioning
confidence: 99%